Pemanfaatan API Midtrans Dan RajaOngkir Dalam Sistem Penjualan Online - Fachmi Maulana; Esron Rikardo Nainggolan; Mulia Rahmayu (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2024)
Pandawa Musik is a shop that runs a business in the field of buying and selling musical instruments. The store has been around for a long time and has quite a number of regular customers. The sales system that runs on Pandawa Musik is still running manually so that there are often problems in data collection and stock checking. And the sales system is still placed in shop windows, distributing flyers or word of mouth. This allows for errors in data collection, the length of the service process and the lack of sales volume. Based on the description above, the authors are interested in developing an information system that can help Pandawa Musik in making web-based E-Commerce, equipped with features that can make work easier and more systematic, especially in the field of data collection and transactions as well as postage throughout Indonesia. From this research, the authors raised the title "Online Sales Information System for Musical Instruments at the Web-Based Pandawa Musik Shop Using the MIDTRANS and RajaOngkir APIs".